IMPLIKASI KOMUNIKASI ANTAR AGAMA DALAM MENINGKATKAN TOLERANSI PADA TRADISI NGABEN PURA DALEM ARSANA PAGESANGAN BARAT KOTA MATARAMA - dayu sakbaniah; Dian Ferdinawan; Nurbaiti; Siti Nurul Yaqinah (AL-IDZAAH: Jurnal Dakwah dan Komunikasi, 2024)
This study is intended to find the implications of interfaith communication, community response, and communication barriers in the Ngaben tradition at Pura Dalem Arsana, West Pageangan, Mataram City, in increasing tolerance. The method used in the study was descriptive qualitative, with data obtained through non-participant observation, as well as in-depth interviews with 11 key informants, along with other supporting data related to this study. The results showed that the implications of interfaith communication carried out in the Ngaben tradition were based on positive and negative responses and internal and external obstacles in the communication process. In fact, one of the benefits of the process can increase tolerance between religious communities.